Study on Time Overrun related to Construction Projects in Sri Lanka - Arulvel, Yathupriyan; Widisinghe, Sankha (Advances in Technology, 2022)
The time overrun in construction projects is a common issue around the world and no exception in Sri Lankan construction industry. The aims are to identify the causes and their significance to the project time overrun as well as to provide suggestions for those identified causes. Totally 39 significant factors were identified as relevant to Sri Lankan construction industry through a literature survey. Then a quantitative questionnaire approach was conducted to identify the significance of factors from industry professionals (civil engineers, quantity surveyors, technical officers, supervisors & directors, and the persons with minimum qualification and experience in the construction industry) working as stakeholders such as clients, consultants, and contractors without considering the project type. The previously identified 39 factors were found to be applicable to the Sri Lankan construction industry with survey results. Through the survey, 33 responses were collected and analyzed based on the relative important index of the results. Highly weighted 15 project time overrun factors were analyzed in detail. Mainly, three factors of time overrun in construction projects were identified by ranking based on overall responses; i) contractor’s improper planning, ii) mistakes during construction by contractors, and iii) delay in preparation and approval of drawings. At the same time, social and cultural factors and disputes with surroundings or neighbours got the least significance based on ranking. The relationship between the significance of factors and relevance to the construction party (contractor, consultant) is also identified in this study. From questionnaire responses, the political influence, material theft, labor attitudes and motivation, and unexpected material cost increase than the total budget was selected for the further discussion. Finally, recommendations are provided for future development projects such as the contractor’s proper planning. As well as experienced and well knowledge professional to be appointed as a project manager by contracting firm.